2016
DOI: 10.21744/ijllc.v2i3.237
|View full text |Cite
|
Sign up to set email alerts
|

Tourism Development Basis in Traditional Village of Kuta

Abstract: Tourism in the Kuta District, located in southern Bali, Indonesia, is a phenomenal global commercial sector that continues to be the largest contributor to Indonesia’s tourism industry, and thereby also contributes to the overall gross national product (GNP) in Indonesia. Kuta’s world renowned tourist destination has its roots dating from the early 19th century, when at that time the island of Bali enticed tourists that had the unique Balinese cultural experiences at heart. Today, Kuta has many sectors of tour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
0
11
0
2
Order By: Relevance
“…THK is a universal concept that grows without formally mentioned in Balinese holy manuscripts for religious references like Gita, Weda, or Sarasamuscaya. It has been widely introduced as Balinese cultural capital implemented in Balinese tourism development (Sumadi, 2016;Purnaya, 2016;Astuti et al, 2018. Its existence as an omnipresent concept was developed along with other Balinese philosophies as a life practice.…”
Section: Tri Hita Karana (Thk)mentioning
confidence: 99%
See 1 more Smart Citation
“…THK is a universal concept that grows without formally mentioned in Balinese holy manuscripts for religious references like Gita, Weda, or Sarasamuscaya. It has been widely introduced as Balinese cultural capital implemented in Balinese tourism development (Sumadi, 2016;Purnaya, 2016;Astuti et al, 2018. Its existence as an omnipresent concept was developed along with other Balinese philosophies as a life practice.…”
Section: Tri Hita Karana (Thk)mentioning
confidence: 99%
“…j The studies include Aditya and Kusuma (2019), Adityanandana (2017), Agung et al (2020), Arjawa and Jayantiari (2017), Atmadja et al (2019), Budhiastra (2016), Ernawati (2015), Gandhiadi et al (2017), Sedana (2020), Ginaya et al (2019), Hariana andKasiyan (2018), Iswari et al (2018), Kusuma et al (2018), Lanya et al (2017), Lorenzen and Lorenzen (2005), Coordinating Ministry of Human Development and Culture Republic of Indonesia (2015), Mudana et al (2018), Narottama et al (2018), Norken et al (2017), Parker (2011), Pickel-Chevalier and Budarma (2016) , Purnaya, (2016), Satya and Lase (2018), Siadis (2014), Astuti et al (2018), Suamba and Sutama (2017), Suarniati et al (2019), Suartika (2005), Sukarma (2016), Sumadi (2016), Sutawan (2004), Suweta (2015), Triyuni et al (2019), Vita et al (2018), Wiranata et al (2012), Wesnawa and Suastra (2016), Wijaya and Artajaya (2020), Wright (2019). k For the different point of view in using world over the field analysis can be seen in Bottero and Crossley (2011).…”
Section: The Thk's Fieldsmentioning
confidence: 99%
“…Basically, the European culture context was different from the one in Indonesia. In Indonesia, Sumadi (2012) found that cultural capital became the basis of tourism sustainability that was able to encourage economic growth in the community. This indicated that tourism affected the livelihoods of people around the touristy destinations, while mobilizing access to certain forms of capital.…”
Section: The Role Of Ritual Capital In Rural Livelihood and Sustainabmentioning
confidence: 99%
“…This study raises the reality that occurs in the field relating to the problem of utilizing telecommunications which are one of the traditional open spaces into a place of business. The swift influence of global culture entering the Ubud region has implications for the occurrence of capitalist ideological practices within the framework of the tourism industry, such as the emergence of the culture industry, popular culture, lifestyle, and consumerism culture (Sumadi, 2016;Indiani & Suda, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%